2006
DOI: 10.1111/j.1075-122x.2006.00240.x
|View full text |Cite
|
Sign up to set email alerts
|

Local Recurrence of Breast Cancer after Skin-Sparing Mastectomy Following Core Needle Biopsy: Case Reports and Review of the Literature

Abstract: The latest advances in diagnostic and therapeutic procedures for breast cancer have provided valuable technological breakthroughs. Yet the long-term consequences of these modern methods are still quite unclear. Such is the case for stereotactic or ultrasound-guided histologic needle biopsy and skin-sparing mastectomy. We report on three patients who presented with multicentric breast cancer diagnosed by stereotactic needle biopsy and treated by skin-sparing mastectomy. All three patients developed recurrence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 18 publications
1
48
1
Order By: Relevance
“…This seeding is not clinically relevant since the host immune system will eliminate most surviving tumor cells, as will subsequent surgery, radio or chemotherapy [2]. Skin sparing mastectomy however offers a different scenario with AE 5% observed local recurrences within the biopsy tract [3]. Treatment options are frequently limited with regard to previous surgery and adjuvant therapies.…”
Section: Introductionmentioning
confidence: 99%
“…This seeding is not clinically relevant since the host immune system will eliminate most surviving tumor cells, as will subsequent surgery, radio or chemotherapy [2]. Skin sparing mastectomy however offers a different scenario with AE 5% observed local recurrences within the biopsy tract [3]. Treatment options are frequently limited with regard to previous surgery and adjuvant therapies.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of excising previous percutaneous biopsy sites is highlighted by evidence of LR at the needle entry site. However, this is not routinely undertaken by all surgeons [4]. SSM can facilitate IBR, utilising the native skin envelope optimises the final contour of the reconstructed breast, resulting in excellent cosmesis, minimising scarring and post-mastectomy deformity, decreasing the skin donor area and reducing the need for contralateral breast adjustment in order to achieve symmetry [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, although the chance is small, this procedure may be followed by implantation of a malignant neoplasm along the biopsy needle tract [1,[6][7][8][9][13][14][15][16]. Some investigators have reported the frequency to be 2% to 38% (Table 2) [6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Several cases of local recurrence caused by CNB have been reported [13,14,16], but some investigators have reported that the CNB technique had no impact on local recurrence after breastconserving surgery with postoperative radiotherapy, and that postoperative radiation therapy may control microscopic seeding in the needle tact [2][3][4][5]. Although Diaz et al reported that the inverse relationship between the amount of displacement observed and time to excision suggested that tumor cells do not survive displacement [6], the impact of needle tract seeding on the local recurrence and overall survival rates of patients after breast-conserving surgery without radiation has not been fully investigated.…”
Section: Discussionmentioning
confidence: 99%